2017
DOI: 10.4038/sljch.v46i4.8381
|View full text |Cite
|
Sign up to set email alerts
|

Why do mothers fail to breastfeed successfully? A descriptive study done at selected lactation management centres in Sri Lanka

Abstract: Background: Exclusive breastfeeding (BF) up to six months is recommended in Sri Lanka because it is known to be the best food for the infants and it provides vast benefits to the mother as well. Since exclusive BF rates decline with the advancing age of the baby, it is quite obvious that mothers face difficulties in BF.Objective: To describe the factors associated with difficulties in BF in mothers with neonates attending selected lactation management centres in the Colombo district. 2 . A study in the United … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Hackman et al (2015) reported primiparity as a risk factor for PIM. High exclusive breastfeeding rates at 6 months suggest that a vast majority of Sri Lankan primiparous mothers eventually end up breastfeeding successfully even if they struggle with breastfeeding initially (Fernando & Prathapan, 2017). It is possible that having this previous experience gives the multiparous mothers confidence in breastfeeding in subsequent childbirths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hackman et al (2015) reported primiparity as a risk factor for PIM. High exclusive breastfeeding rates at 6 months suggest that a vast majority of Sri Lankan primiparous mothers eventually end up breastfeeding successfully even if they struggle with breastfeeding initially (Fernando & Prathapan, 2017). It is possible that having this previous experience gives the multiparous mothers confidence in breastfeeding in subsequent childbirths.…”
Section: Discussionmentioning
confidence: 99%
“…These beliefs and expectations make mothers feel that their milk supply is inadequate, especially in the first few days, until lactogenesis II has occurred. A recent study in Sri Lanka (Fernando & Prathapan, 2017) revealed “living in an extended family” as a risk factor for having difficulties in breastfeeding.…”
Section: Introductionmentioning
confidence: 99%